Wear-resistant anticorrosive flame-retardant coating for wooden building and preparation method of wear-resistant anticorrosive flame-retardant coating

Through the synergistic effect of the composite flame retardant GUPSi and chlorotriazine DACT in wooden building coatings, combined with zinc oxide-titanium dioxide-graphene composite materials, environmental pollution caused by excessive flame retardant in existing coatings and The problem of mechanical performance degradation has achieved efficient and economical flame retardant, corrosion protection and mechanical performance improvement.

CN119490777APending Publication Date: 2025-02-21SHANGHAI TECHN INST OF ELECTRONICS & INFORMATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411834163.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The addition of a large amount of flame retardant to existing wooden building coatings leads to environmental pollution and mechanical performance degradation, while increasing costs, making it difficult to maintain good flame retardant and mechanical performance at the same time.

Method used

Using the synergistic effect of the composite flame retardant GUPSi and chlorotriazine DACT, combined with zinc oxide-titanium dioxide-graphene composite material, a wear-resistant anti-corrosion flame retardant coating was prepared, which increased the coating film by reducing the amount of flame retardant added. flame retardant, corrosion-proof and mechanical properties.

Benefits of technology

It significantly reduces the amount of flame retardant added, while maintaining the good flame retardant effect of the paint, improving the salt spray resistance, corrosion resistance and mechanical properties of the coating, and is suitable for a variety of complex scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a wear-resistant, corrosion-resistant and flame-retardant coating for a wooden building. The wear-resistant, corrosion-resistant and flame-retardant coating is prepared from the following raw materials in percentage by mass: 30 to 50 percent of acrylate emulsion, 0.5 to 1 percent of thickening agent, 0.5 to 1 percent of dispersing agent, 0.2 to 0.5 percent of defoaming agent, 15 to 25 percent of composite flame retardant GUPSi, 3 to 5 percent of chlorinated triazine DACT, 4 to 8 percent of zinc oxide-titanium dioxide-graphene composite material and the balance of water. The composite flame retardant GUPSi has a good flame retardant effect and good compatibility with a water-based acrylate system, and when the composite flame retardant GUPSi and the chlorinated triazine DACT are compounded for use, a synergistic effect can be generated, so that the coating system has a good flame retardant effect and salt spray resistance. By adding the zinc oxide-titanium dioxide-graphene composite material, the tensile strength and the elongation at break of a coating film are effectively improved, so that the coating film is not easy to tear or peel off, and meanwhile, the coating film has excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings for wooden buildings, and in particular to a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings and a preparation method thereof. Background Art

[0002] Wood is a common building material with many advantages such as natural environmental protection, affordable price, and easy processing. However, wood also has its natural defects: first, wood has good flammability. When a fire occurs, the fire spreads rapidly under the condition of sufficient oxygen, and it is easy to become uncontrollable; second, after being exposed to wind and sun for a long time, wood is prone to expansion, deformation, rot and deterioration. Therefore, it is very necessary to carry out corresponding flame retardant, anti-corrosion, and anti-deformation treatments on the surface of wooden buildings. Taking flame retardancy as an example, coating the surface of wood with flame retardant coating is a conventional method to solve the problem of wood flammability, but when flame retardants are applied to acrylic emulsion coating systems, a large amount of them usually need to be added to achieve a good flame retardant effect. However, adding a large amount of flame retardants to the coating is not only easy to cause environmental pollution problems, but also cause the mechanical properties of the coating to decrease, and at the same time increase the cost of the coating. Therefore, how to reduce the amount of flame retardants in the coating and keep the coating film with good mechanical properties and flame retardant properties is a difficult problem to be solved in the field of coatings. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings, comprising the following raw materials in percentage by mass: 30-50% of acrylic emulsion, 0.5-1% of thickener, 0.5-1% of dispersant, 0.2-0.5% of defoamer, 15-25% of composite flame retardant GUPSi, 3-5% of chlorotriazine DACT, 4-8% of zinc oxide-titanium dioxide-graphene composite material, and the balance of water.

[0004] The raw materials for preparing the composite flame retardant GUPSi are dicyandiamide, phosphoric acid, silica sol and water, and the preparation method is as follows: first, dicyandiamide, phosphoric acid and water react at a reaction temperature of 90° C. to 120° C. to synthesize guanyl urea phosphate, and then, the composite flame retardant GUPSi is prepared by compounding the guanyl urea phosphate and silica sol.

[0005] Preferably, the thickener is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, the dispersant is one or more of sodium lignin sulfonate, sodium lauryl sulfate, sodium methylene dinaphthalene sulfonate and sodium dibutylnaphthalene sulfonate, and the defoamer is one or more of Foamaster306, Nopco 8034L and Foamex800.

[0006] Preferably, the weight ratio of guanyl urea phosphate to the dry weight of silica sol is 1:(0.2-0.4), and the molar ratio of dicyandiamide, phosphoric acid and water is dicyandiamide:phosphoric acid:water=1:(0.8-1.2):(20-50).

[0007] Preferably, after the reaction for synthesizing guanyl urea phosphate is completed, the reaction mixture can be separated by crystallization and filtration, and the filtrate can be recycled.

[0008] The preparation method of the zinc oxide-titanium dioxide-graphene composite material is:

[0009] (1) 5-20 mL of butyl phthalate is added to 500 mL of anhydrous ethanol and mixed, and then dilute nitric acid is slowly added dropwise until the pH value is 3-4, and the mixture is mixed to obtain a pre-prepared solution A;

[0010] (2) 2-5 L of a 7-9 mg / mL graphene oxide aqueous solution was placed in a 10 L reactor, 2 L of water was added and ultrasonicated for 30-60 min, 10-20 g of zinc salt was weighed and added to the reactor, the mixture was stirred thoroughly and ultrasonicated for 1-1.5 h, and the pH was adjusted to 10-11 with concentrated ammonia water to obtain a pre-formulated solution B;

[0011] (3) Add the pre-prepared liquid A to the reactor and mix it with the pre-prepared liquid B, then add 10-20g of the reducing agent, stir for 30-60min, heat the reactor to 160-190°C, keep it warm for 8-10h, filter and wash it with deionized water for 3 times and anhydrous ethanol for 3 times, and then transfer it to an oven and dry it at 50°C to obtain a zinc oxide-titanium dioxide-graphene composite material.

[0012] The dosage of butyl phthalate is 10-15 mL, the dosage of zinc acetate is 10-13 g, and the dosage of graphene oxide aqueous solution is 3-4 L; the zinc salt is zinc acetate or zinc nitrate; and the reducing agent is glucose.

[0013] In the step (2), the first ultrasonic treatment lasts for 30 minutes, and the second ultrasonic treatment lasts for 1.5 hours. In the step (3), the reactor is heated to 180° C. and kept warm for 9 hours.

[0014] A method for preparing a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings comprises the following steps:

[0015] (1) using an oven to sequentially dry the composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material at 80-90° C. for 1-2 h, mixing the dried composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material and grinding them thoroughly to obtain powder;

[0016] (2) mixing the acrylic emulsion, thickener, dispersant, defoamer and water, and then shearing and stirring for 5-10 minutes at a shear rate of 500-1500 r / min to obtain a mixed solution;

[0017] (3) Add the powder obtained in step (1) to the mixed solution in step (2), and shear and stir for 20-30 minutes at a shear rate of 1500-2000 r / min to prepare a wear-resistant, anti-corrosion and flame-retardant coating.

[0018] In the step (1), the drying temperature is 90° C. and the drying time is 1.5 h; in the step (2), the shear stirring time is 8 min and the shear rate is 1000 r / min.

[0019] In the step (3), the shear stirring time is 25 min and the shear rate is 2000 r / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention prepares a composite flame retardant GUPSi, which has good flame retardant effect. More importantly, the composite flame retardant has good compatibility with the water-based acrylate system, and the preparation process is simple, which is suitable for large-scale industrial production.

[0022] (2) The present invention uses a composite flame retardant GUPSi and a chlorotriazine DACT in combination, and a composite flame retardant GUPSi-chlorotriazine DACT composition with a specific content can produce a synergistic effect. The experimental results show that through the synergistic effect of the two, the amount of flame retardant added can be significantly reduced while maintaining the coating with a good flame retardant effect. In addition, chlorotriazine DACT is a chlorine-containing organic substance. After adding this component, the salt spray resistance and corrosion resistance of the coating can also be improved, so that the coating can withstand harsh environments, so that it can be applied to a variety of complex scenes.

[0023] (3) The present invention effectively improves the tensile strength and elongation at break of the coating by adding zinc oxide-titanium dioxide-graphene composite materials, making the coating less likely to be torn or peeled off, while having good wear resistance and being able to better resist the influence of the external environment on wooden buildings. DETAILED DESCRIPTION

[0024] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0025] The acrylate emulsion in the present invention can use commercially available acrylate emulsions for water-based coatings, such as BASF Acronal 7016G, BASF Acronal PA510, BASF Acronal LR 8960, and the like.

[0026] The preparation method of the composite flame retardant GUPSi is as follows: dicyandiamide, phosphoric acid, silica sol and water are used as raw materials, wherein dicyandiamide, phosphoric acid and water are reacted at a reaction temperature of 90° C. to 120° C. to synthesize guanylurea phosphate, and then the composite flame retardant is prepared by compounding the guanylurea phosphate and silica sol. The weight ratio of the guanylurea phosphate to the dry weight of the silica sol is 1:0.3, and the molar ratio of dicyandiamide, phosphoric acid and water is dicyandiamide: phosphoric acid: water=1:1:30.

[0027] Example 1

[0028] A wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings comprises the following raw materials in percentage by mass: 40% of acrylic emulsion (BASF Acronal PA510), 0.8% of hydroxyethyl cellulose, 0.6% of sodium lauryl sulfate, 0.3% of Foamaster306, 20% of composite flame retardant GUPSi, 4% of chlorotriazine DACT, 6% of zinc oxide-titanium dioxide-graphene composite material, and the balance of water.

[0029] The preparation method of the zinc oxide-titanium dioxide-graphene composite material is:

[0030] (1) 5-20 mL of butyl phthalate is added to 500 mL of anhydrous ethanol and mixed, and then dilute nitric acid is slowly added dropwise until the pH value is 3, and the pre-prepared solution A is obtained after mixing;

[0031] (2) 3 L of 8.3 mg / mL graphite oxide ink solution was placed in a 10 L reactor, 2 L of water was added and ultrasonicated for 45 min, then 10.42 g of zinc salt was weighed and added to the reactor, the mixture was stirred thoroughly and ultrasonicated for 1.5 h, and the pH was adjusted to 10.7 with concentrated ammonia water to obtain pre-formulated solution B;

[0032] (3) Add the pre-prepared liquid A into the reactor and mix it with the pre-prepared liquid B, then add 10 g of glucose as a reducing agent, stir for 30 min, heat the reactor to 180° C., keep it warm for 9 h, filter and wash it with deionized water for 3 times, wash it with anhydrous ethanol for 3 times, and then transfer it to an oven and dry it at 50° C. to obtain a zinc oxide-titanium dioxide-graphene composite material.

[0033] The preparation method of wood flame retardant coating is as follows:

[0034] (1) using an oven to sequentially dry the composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material at 85° C. for 1.5 h, mixing the dried composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material and grinding them thoroughly to obtain powder;

[0035] (2) mixing the acrylic emulsion, thickener, dispersant, defoamer and water, and then shearing and stirring for 8 minutes at a shear rate of 1000 r / min to obtain a mixed solution;

[0036] (3) Add the powder obtained in step (1) to the mixed solution in step (2), and shear and stir for 25 minutes at a shear rate of 2000 r / min to prepare a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings.

[0037] Example 2

[0038] A wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings comprises the following raw materials in percentage by mass: 30% acrylic emulsion (BASF Acronal LR 8960), 0.5% hydroxymethyl cellulose, 0.5% sodium lignin sulfonate, 0.2% Nopco8034L, 25% composite flame retardant GUPSi, 3% chlorotriazine DACT, 4% zinc oxide-titanium dioxide-graphene composite material, and the balance is water.

[0039] The preparation method of the zinc oxide-titanium dioxide-graphene composite material is:

[0040] (1) 5-20 mL of butyl phthalate is added to 500 mL of anhydrous ethanol and mixed, and then dilute nitric acid is slowly added dropwise until the pH value is 4, and the mixture is mixed to obtain a pre-prepared solution A;

[0041] (2) 3 L of 8.3 mg / mL graphite oxide ink solution was placed in a 10 L reactor, 2 L of water was added and ultrasonicated for 45 min, then 10.42 g of zinc salt was weighed and added to the reactor, the mixture was stirred thoroughly and ultrasonicated for 1.5 h, and the pH was adjusted to 10.7 with concentrated ammonia water to obtain pre-formulated solution B;

[0042] (3) Add the pre-prepared liquid A into the reactor and mix it with the pre-prepared liquid B, then add 10 g of glucose as a reducing agent, stir for 30 min, heat the reactor to 180 ° C, keep it warm for 9 h, filter and wash it with deionized water for 3 times, wash it with anhydrous ethanol for 3 times, and transfer it to an oven to dry at 50 ° C to obtain a zinc oxide-titanium dioxide-graphene oxide composite material.

[0043] The preparation method of wood flame retardant coating is as follows:

[0044] (1) using an oven to sequentially dry the composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material at 80° C. for 2 h, mixing the dried composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material and grinding them thoroughly to obtain powder;

[0045] (2) mixing the acrylic emulsion, thickener, dispersant, defoamer and water, and then shearing and stirring for 5 minutes at a shear rate of 1500 r / min to obtain a mixed solution;

[0046] (3) Add the powder obtained in step (1) to the mixed solution in step (2), and shear and stir for 20 minutes at a shear rate of 2000 r / min to prepare a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings.

[0047] Example 3

[0048] The invention discloses a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings, comprising the following raw materials in percentage by mass: 50% of acrylic emulsion (BASF Acronal 7016G), 1% of hydroxypropyl cellulose, 1% of sodium methylene dinaphthalene sulfonate, 0.5% of Foamex 8000, 15% of composite flame retardant GUPSi, 5% of chlorotriazine DACT, 8% of zinc oxide-titanium dioxide-graphene composite material, and the balance of water.

[0049] The preparation method of the zinc oxide-titanium dioxide-graphene composite material is:

[0050] (1) 5-20 mL of butyl phthalate is added to 500 mL of anhydrous ethanol and mixed, and then dilute nitric acid is slowly added dropwise until the pH value is 3, and the pre-prepared solution A is obtained after mixing;

[0051] (2) 3 L of 8.3 mg / mL graphite oxide ink solution was placed in a 10 L reactor, 2 L of water was added and ultrasonicated for 45 min, then 10.42 g of zinc salt was weighed and added to the reactor, the mixture was stirred thoroughly and ultrasonicated for 1.5 h, and the pH was adjusted to 10.7 with concentrated ammonia water to obtain pre-formulated solution B;

[0052] (3) Add the pre-prepared liquid A into the reactor and mix it with the pre-prepared liquid B, then add 10 g of glucose as a reducing agent, stir for 30 min, heat the reactor to 180 ° C, keep it warm for 9 h, filter and wash it with deionized water for 3 times, wash it with anhydrous ethanol for 3 times, and transfer it to an oven to dry at 50 ° C to obtain a zinc oxide-titanium dioxide-graphene oxide composite material.

[0053] The preparation method of wood flame retardant coating is as follows:

[0054] (1) using an oven to sequentially dry the composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material at 90° C. for 1 h, mixing the dried composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material and grinding them thoroughly to obtain powder;

[0055] (2) mixing the acrylic emulsion, thickener, dispersant, defoamer and water, and then shearing and stirring for 10 minutes at a shear rate of 500 r / min to obtain a mixed solution;

[0056] (3) Add the powder obtained in step (1) to the mixed solution in step (2), and shear and stir for 30 minutes at a shear rate of 1500 r / min to prepare a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings.

[0057] Comparative Example 1

[0058] The only difference from Example 1 is that the composite flame retardant GUPSi is 35%, and the chlorotriazine DACT is 0%.

[0059] Comparative Example 2

[0060] The only difference from Example 1 is that the composite flame retardant GUPSi is 24%, and the chlorotriazine DACT is 0%.

[0061] Comparative Example 3

[0062] The only difference from Example 1 is that the composite flame retardant GUPSi contains 16% and the chlorotriazine DACT contains 8%.

[0063] Comparative Example 4

[0064] The only difference from Example 1 is that the composite flame retardant GUPSi is 8% and the chlorotriazine DACT is 16%.

[0065] Comparative Example 5

[0066] The only difference from Example 1 is that the composite flame retardant GUPSi is 0%, and the chlorotriazine DACT is 24%.

[0067] Comparative Example 6

[0068] The only difference from Example 1 is that the zinc oxide-titanium dioxide-graphene composite material is 0%.

[0069] Comparative Example 7

[0070] The only difference from Example 1 is that the zinc oxide-titanium dioxide-graphene composite material is 2%.

[0071] Comparative Example 8

[0072] The only difference from Example 1 is that the zinc oxide-titanium dioxide-graphene composite material is 10%.

[0073] The wood boards were coated and dried under the same conditions using the wood flame retardant coatings prepared in Examples 1-3 and Comparative Examples 1-5. The wood board flame retardancy test was conducted using a JF-3 oxygen index tester in accordance with GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test" for limiting oxygen index test.

[0074] Immerse the wood board in 3% sodium chloride solution at room temperature, observe the condition of the paint film every 12 hours until the paint film starts to bubble or fall off, and record the corresponding time to characterize the salt spray resistance of the coating.

[0075] The wood sticks were coated and dried under the same conditions using the wood flame retardant coatings prepared in the above embodiments and comparative examples, and the coated wood sticks were placed on a combustion plate containing alcohol in a combustion cabinet, ignited and burned for 100 seconds and then extinguished, and the weight loss rate and carbonization height of the wood sticks were measured.

[0076] The test results are shown in Table 1:

[0077] Table 1

[0078] Oxygen index / % Salt spray resistance / h Combustion weight loss rate / % Carbonization height / cm Example 1 40.5 300 0.62 4.7 Example 2 41.3 324 0.58 4.4 Example 3 40.9 312 0.63 4.5 Comparative Example 1 33.5 180 0.82 5.9 Comparative Example 2 33.2 192 0.86 6.1 Comparative Example 3 34.6 264 0.79 5.8 Comparative Example 4 28.3 240 0.97 7.1 Comparative Example 5 23.8 216 1.13 8.5

[0079] From the experimental results in Table 1, it can be seen that compounding the composite flame retardant GUPSi and chlorotriazine DACT in an appropriate ratio can not only significantly improve the flame retardant properties of the coating, but also improve the corrosion resistance and salt spray resistance of the coating. However, the total amount and the amount of each addition need to be within the appropriate range. Taking chlorotriazine DACT as an example, adding too much or too little will significantly reduce the compatibility of the coating system, causing the performance of the coating film to decline. 3-5% is the appropriate addition amount.

[0080] The wood flame retardant coatings prepared in Examples 1-3 and Comparative Examples 6-8 were prepared into dumbbell-shaped test pieces with a thickness of 2.0 mm, and their tensile strength and elongation at break were measured. The weight loss rate of the coatings was measured using a rotating friction rubber wheel method to characterize their wear resistance.

[0081] The test results are shown in Table 2:

[0082] Table 2

[0083] Tensile strength / MPa Elongation at break / % Wear weight loss rate / % Example 1 3.32 266 1.65 Example 2 3.25 257 1.69 Example 3 3.41 259 1.53 Comparative Example 6 2.50 218 2.58 Comparative Example 7 2.72 237 2.39 Comparative Example 8 2.81 226 2.16

[0084] It can be seen from the experimental results in Table 2 that the mechanical properties and wear resistance of the coating can be significantly improved by adding an appropriate amount of zinc oxide-titanium dioxide-graphene composite material, but excessive addition of zinc oxide-titanium dioxide-graphene composite material will lead to poor elasticity of the coating, thereby causing the mechanical properties and wear resistance of the coating to be significantly reduced. 4-8% is an appropriate addition amount.

[0085] The technical solution of the present invention can be used to prepare a wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings with excellent fire-proof, anti-corrosion, wear-resistant and mechanical properties, and has broad application prospects in the field of wooden buildings.

[0086] Finally, it should be noted that the embodiments are only the best specific implementation methods of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions recorded in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wear-resistant, anti-corrosion and flame-retardant coating for wooden buildings, characterized in that: The invention comprises the following raw materials in percentage by mass: 30-50% of acrylic emulsion, 0.5-1% of thickener, 0.5-1% of dispersant, 0.2-0.5% of defoamer, 15-25% of composite flame retardant GUPSi, 3-5% of chlorotriazine DACT, 4-8% of zinc oxide-titanium dioxide-graphene composite material, and the balance of water.

2. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 1, characterized in that: The raw materials for preparing the composite flame retardant GUPSi are dicyandiamide, phosphoric acid, silica sol and water, and the preparation method is as follows: first, dicyandiamide, phosphoric acid and water react at a reaction temperature of 90° C. to 120° C. to synthesize guanyl urea phosphate, and then, the composite flame retardant GUPSi is prepared by compounding the guanyl urea phosphate and silica sol.

3. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 2, characterized in that: The weight ratio of guanyl urea phosphate to the dry weight of silica sol is 1:(0.2-0.4), and the molar ratio of dicyandiamide, phosphoric acid and water is dicyandiamide:phosphoric acid:water=1:(0.8-1.2):(20-50).

4. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 1, characterized in that: The thickener is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, the dispersant is one or more of sodium lignin sulfonate, sodium lauryl sulfate, sodium methylene dinaphthalene sulfonate and sodium dibutylnaphthalene sulfonate, and the defoamer is one or more of Foamaster306, Nopco 8034L and Foamex800.

5. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 1, characterized in that: The preparation method of the zinc oxide-titanium dioxide-graphene composite material is: (1) 5-20 mL of butyl phthalate is added to 500 mL of anhydrous ethanol and mixed, and then dilute nitric acid is slowly added dropwise until the pH value is 3-4, and the mixture is mixed to obtain a pre-prepared solution A; (2) 2-5 L of a 7-9 mg / mL graphene oxide aqueous solution was placed in a 10 L reactor, 2 L of water was added and ultrasonicated for 30-60 min, 10-20 g of zinc salt was weighed and added to the reactor, the mixture was stirred thoroughly and ultrasonicated for 1-1.5 h, and the pH was adjusted to 10-11 with concentrated ammonia water to obtain a pre-formulated solution B; (3) Add the pre-prepared liquid A to the reactor and mix it with the pre-prepared liquid B, then add 10-20g of the reducing agent, stir for 30-60min, heat the reactor to 160-190°C, keep it warm for 8-10h, filter and wash it with deionized water for 3 times and anhydrous ethanol for 3 times, and then transfer it to an oven and dry it at 50°C to obtain a zinc oxide-titanium dioxide-graphene composite material.

6. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 5, characterized in that: The dosage of the butyl phthalate is 10-15 mL, the dosage of the graphene oxide aqueous solution is 3-4 L, the zinc salt is zinc acetate or zinc nitrate, the dosage of the zinc salt is 10-13 g, and the reducing agent is glucose.

7. The wear-resistant, anti-corrosion and flame-retardant coating according to claim 5, characterized in that: In the step (2), the first ultrasonic treatment lasts for 30 minutes, and the second ultrasonic treatment lasts for 1.5 hours. In the step (3), the reactor is heated to 180° C. and kept warm for 9 hours.

8. A method for preparing the wear-resistant, anti-corrosion and flame-retardant coating according to any one of claims 1 to 7, comprising the following steps: (1) using an oven to sequentially dry the composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material at 80-90° C. for 1-2 h, mixing the dried composite flame retardant GUPSi, chlorotriazine DACT and zinc oxide-titanium dioxide-graphene composite material and grinding them thoroughly to obtain powder; (2) mixing the acrylic emulsion, thickener, dispersant, defoamer and water, and then shearing and stirring for 5-10 minutes at a shear rate of 500-1500 r / min to obtain a mixed solution; (3) Add the powder obtained in step (1) to the mixed solution in step (2), and shear and stir for 20-30 minutes at a shear rate of 1500-2000 r / min to prepare a wear-resistant, anti-corrosion and flame-retardant coating.

9. The preparation method according to claim 8, wherein the drying temperature in step (1) is 90°C and the drying time is 1.5 hours; the shear stirring time in step (2) is 8 minutes and the shear rate is 1000 r / min.

10. The preparation method according to claim 8, wherein the shear stirring time in step (3) is 25 min and the shear rate is 2000 r / min.

Citation Information

Patent Citations

  • Water-soluble timber flame retardant, preparation method and applications thereof

    CN104708690A

  • Anti-corrosion coating containing grapheme / zinc oxide / titanium oxide composite material and preparation method thereof

    CN105419413A

  • Method for solving problems of moisture absorption and stickiness of phosphorus coated fabric by adding inorganic components

    CN105907210A

  • Fireproof and flame-retardant water-based coating for bamboo and wood products, and preparation method thereof

    CN108504222A

  • Water-based paint and preparation method thereof

    CN110669397A